2015
DOI: 10.1159/000369509
|View full text |Cite
|
Sign up to set email alerts
|

Gluten-Related Disorders: Gluten Ataxia

Abstract: The term gluten-related disorders (GRD) refers to a spectrum of diverse clinical manifestations triggered by the ingestion of gluten in genetically susceptible individuals. They include both intestinal and extraintestinal manifestations. Gluten ataxia (GA) is one of the commonest neurological manifestations of GRD. It was originally defined as otherwise idiopathic sporadic ataxia in the presence of circulating antigliadin antibodies of IgA and/or IgG type. Newer more specific serological markers have been iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 33 publications
3
49
0
4
Order By: Relevance
“…It is also possible that the new diets improved the Border Terriers’ general health status and reduced their stress; in fact, 28% of the dogs in this study presented recurrent skin and ear problems and 16% of the dogs had recurrent gastrointestinal problems, which may be associated with an underlying food hypersensitivity. However, there is mounting evidence of an influence of the brain‐gut‐microbiome axis on central nervous system neurotransmission, and enteric glial cells have been involved in the pathophysiology of gastrointestinal disease, such inflammatory bowel disease, gluten ataxia, but also Parkinson's disease . An association between diet and severity of Border Terrier attacks, as suggested by our findings and Black et al's study, needs to be verified with a prospective study; however, if this hypothesis was to be confirmed, the Border Terrier dogs could represent an ideal spontaneous model to investigate the effects of diet on paroxysmal dyskinesias.…”
Section: Discussionsupporting
confidence: 51%
“…It is also possible that the new diets improved the Border Terriers’ general health status and reduced their stress; in fact, 28% of the dogs in this study presented recurrent skin and ear problems and 16% of the dogs had recurrent gastrointestinal problems, which may be associated with an underlying food hypersensitivity. However, there is mounting evidence of an influence of the brain‐gut‐microbiome axis on central nervous system neurotransmission, and enteric glial cells have been involved in the pathophysiology of gastrointestinal disease, such inflammatory bowel disease, gluten ataxia, but also Parkinson's disease . An association between diet and severity of Border Terrier attacks, as suggested by our findings and Black et al's study, needs to be verified with a prospective study; however, if this hypothesis was to be confirmed, the Border Terrier dogs could represent an ideal spontaneous model to investigate the effects of diet on paroxysmal dyskinesias.…”
Section: Discussionsupporting
confidence: 51%
“…It is considered as one of the commonest neurological manifestations of gluten-related disorders: its prevalence was estimated at 15% amongst all ataxias and 40% of all idiopathic sporadic ataxias . [6]. Its diagnosis should be confirmed by the presence of anti-gliadin antibodies, with or without other serological, autoimmune markers of gluten intolerance (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Its diagnosis should be confirmed by the presence of anti-gliadin antibodies, with or without other serological, autoimmune markers of gluten intolerance (i.e. anti-tissue trnasglutaminase) [6,7]. Early diagnosis and treatment may protect the first group from the development and/or progression of neurological dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGA has been reported in 43% of otherwise idiopathic cerebellar ataxia (IDCA) cases; however, AGA is also found in up to 12% controls and in 13% hereditary ataxia (HA) cases 9 10. When comparing with controls, IDCA cases are thus more commonly reported to have AGA seropositivity 10. However, these results have been inconsistently replicated 3 11–14.…”
Section: Introductionmentioning
confidence: 99%